Workers’ Protection in the Covid-19 Era in Nigeria - Ogbole Ogancha O; Oreoluwa Omotayo Oduniyi (Faculty of Law, Universitas Padjadjaran, 2021)
Against the backdrop of measures adopted sequel to the outbreak of the pandemic, this research focuses on the impact of Covid-19 on the workplace. It highlights and interrogates the utility of responsive measures and also articulates recondite labour issues relating to changing work patterns, pay cuts, job losses culminating in growing unemployment rate, and occupational safety and health concerns within the context of extant labour standards. It also extends focus to the impact of Covid-19 on existing challenges revolving around working poverty, decent work deficit, unfair labour practices, and ineffective labour regimes. This research finds, inter alia, that impact of the Covid-19 pandemic on the workplace is colossal, disruptive, and unprecedented, and that extant labour standards, having proved mute on a wide range of contingent workplace issues, can only provide some sort of protection in a detached manner. The research concludes with an array of far-reaching recommendations on the adoption of protective and remedial legal norms that are transient, flexible, and proactive enough to accommodate diverse situations capable of undermining the prospects for labour laws, regulations, and policies in the Covid-19 era.Perlindungan Pekerja pada Masa Covid-19 di Nigeria AbstrakSehubungan dengan merebaknya pandemi Covid-19, penelitian ini berusaha untuk menjelaskan pengaruh Covid-19 di lingkungan kerja. Penelitian ini menyoroti kebijakan yang dikeluarkan untuk penanganan krisis, serta menggambarkan mengenai permasalahan ketenagakerjaan yang berkaitan dengan perubahan pola kerja, pemotongan gaji, pemutusan hubungan kerja yang menyebabkan tingginya tingkat pengangguran dan kaitannya dengan keselamatan dan kesehatan para pekerja. Lebih jauh lagi, artikel ini juga meneliti dampak Covid-19 di tempat kerja sangat signifikan, dimana hal ini memperparah permasalahan kemisikinan, minimnya pekerjaan yang layak, praktik perburuhan yang tidak adil, dan inefektivitas sistem kerja. Berdasarkan hal tersebut, penulis menyimpulkan bahwa dampak pandemi Covid-19 di tempat kerja sangat besar dan disruptif yang menyebabkan memperburuk masalah ketenagakerjaan. Adapun untuk mewujudkan proteksi kepada para pekerja saat pandemi, penelitian ini merekomendasikan lahirnya norma hukum yang fleksibel dan proaktif guna bisa mengakomodir keberagaman kebutuhan dan memperbaiki kekurangan undang-undang serta kebijakan mengenai ketenagakerjaan di masa Covid-19.Kata Kunci: covid-19, pekerjaan, tempat kerja. DOI: https://doi.org/10.22304/pjih.v8n2.a7